Teoría del caos y educación. Acerca de la reconceptualización del saber educativo - Cañellas, Antonio J. Colom (Revista Española de Pedagogía, 2025)
After canying out a critical analysis of the role of science in modernism which is based on order and specialization, the chaos theory and its more fundamental principles are re-examined by pointing out the importance of this theory for the understanding of complex systems that are non-lineal and unpredictable. With this in mind, similar characteristics are established in educational systems; thus we sense the need for the integration of the chaos theot-y in educational science. Next there is a rethinking of the possible applications of this theo.ry in the areas of personal development, curriculum, learning processes, and administration within the field education, etc. This work concludes with the establishing of the basis for a theory of education that attempts to integrate ali the contributions provided by the chaos theory. Descriptores: education and chaos theory theory of Education and chaos